The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.1017/s0021859600075584
|View full text |Cite
|
Sign up to set email alerts
|

Dietary nitrogen and phosphorus depletion in cattle and their effects on liveweight gain, blood metabolite concentrations and phosphorus kinetics

Abstract: In a 15-week animal-house experiment, 24 steers were offered one of six diets based on molasses and ad libitum barley straw. Three levels of dietary nitrogen (N) and three levels of dietary phosphorus (P), in factorial combination, were formulated by the addition of urea, formaldehyde-treated wheat gluten and monosodium orthophosphate. Food intake, liveweight gain, plasma metabolites and P kinetics were measured under dietary regimens similar to those experienced by cattle grazing Australia's northern semi-ari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
6

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 24 publications
2
24
0
6
Order By: Relevance
“…For example, failing to meet the P requirements of rumen microflora may have a negative effect on ration digestibility and microbial protein synthesis, as reviewed by Breves and Schroder (1991), and this in turn may have a negative effect on food intake. However, reduced food intakes have been observed with cows offered 'low' P diets, despite ration digestibility being unaffected (Milton and Ternouth, 1985;Bortolussi et al, 1996). The latter authors have suggested that this may be mediated via an effect at a cell metabolism level.…”
Section: Discussionmentioning
confidence: 99%
“…For example, failing to meet the P requirements of rumen microflora may have a negative effect on ration digestibility and microbial protein synthesis, as reviewed by Breves and Schroder (1991), and this in turn may have a negative effect on food intake. However, reduced food intakes have been observed with cows offered 'low' P diets, despite ration digestibility being unaffected (Milton and Ternouth, 1985;Bortolussi et al, 1996). The latter authors have suggested that this may be mediated via an effect at a cell metabolism level.…”
Section: Discussionmentioning
confidence: 99%
“…Segundo WITT e OWENS (1983), a disponibilidade de fósforo (P) para os microrganismos do rúmen é importante para atingir a máxima eficiência de digestão dos nutrientes. BORTOLUSSI et al (1996), investigando os efeitos dos níveis de nitrogênio (N) e P na ingestão e no ganho em peso de novilhos confinados, observaram que a adição de N e P na dieta composta de glúten de trigo, melaço, palha de cevada e uréia melhorou o ganho em peso e a ingestão de alimentos de bovinos confinados durante quinze semanas.…”
Section: Introductionunclassified
“…Considerando-se a quantidade de P ingerido, a variação encontrada está próxima às obtidas por Ternouth (1989), Hendricksen et al (1994) e Bortolussi et al (1996), ficando pouco abaixo dos valores observados por Bueno (1997). Isso evidencia que a perda endógena não é um valor constante, como concluíram também outros autores (Braithwaite, 1984;Coates & Ternouth, 1992;Louvandini & Vitti, 1994;Ternouth & Coates, 1997).…”
Section: Methodsunclassified
“…Young et al (1966) observaram que, diferentemente do cálcio, a excreção de fósforo endógeno fecal variou com a quantidade ingerida de P. As perdas de P aumentaram de 16,8 para 24,9 mg/kg PV/dia, quando o conteúdo de P da dieta de bezerros de seis meses aumentou de 12,7 para 31,6 g/dia (Annenkov, 1982). Bortolussi et al (1996) determinaram, em bovinos consumindo entre 6 e 41 mg P/kg PV/dia, perdas endógenas de P variando de 9 a 21 mg/kg PV/dia, as quais foram também relacionadas com a ingestão de matéria seca e P no plasma. No Brasil, Louvandini & Vitti (1994) determinaram 10,65 mg/kg PV/dia para a perda endógena de P, em ovinos de 40 kg de peso vivo, mas o nível mais baixo de P ingerido correspondeu a 51,11 ± 14,45 mg/kg PV/dia, constando também que, a partir de ingestão de 100 mg P/kg PV/dia, há tendência de diminuição nos valores de P endógeno.…”
Section: Introductionunclassified